The Potential of Bioplastic Waste Made From Polybutylene Adipate-Co-Terephthalate (PBAT) as Compost Mixtures - Rachmawati, Siti; Matin, Hashfi Hawali Abdul; Suhardono, Sapta; Daniswara, Agnar Pradipa; Fadhilah, Ririn Nur; Nurlita, Siti (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2026)
Biodegradable bioplastics offer an environmentally friendly alternative. One type of bioplastic being developed is Polybutylene Adipate-Co-Terephthalate (PBAT), an aliphatic-aromatic polyester capable of decomposing through microbial activity. This study aimed to analyze the potential of bioplastic waste as a compost mixture ingredient and determine the optimal composition of bioplastic waste mixtures for compost production. The study utilized a Completely Randomized Design (CRD). The quality of the compost made from bioplastic waste mixtures was evaluated based on SNI 7763:2024 standards, with parameters including pH, temperature, additional substances, and chemical content, such as nitrogen (N), phosphorus (P), potassium (K), and organic carbon (C-organic). The composting process lasted 60 d, using mixtures of bioplastics and cow manure organic waste in proportions of 95:5, 90:10, 85:15, 80:20, 75:25, and 70:30, each weighing 1 kg. Some mixtures were supplemented with 30 mL of activated EM4 to accelerate decomposition, whereas the control group used only cow manure. The results indicate that the compost produced generally met the SNI 7763:2024 standards. The most effective composition was 80% organic waste, 20% bioplastic, and 30 mL EM4. This composition achieved N+P2O5+K2O levels of 2.88%, C-organic content of 30.46%, moisture content of 24.60%, and pH of 7.60.